Determinants of loan Loss Provisioning for commercial banks in HK - Zhang, Yueying (2016)
This paper examines the determinants of loan loss provisions in terms of test hypothesis on business cycle, income smoothing management, regulatory capital management, dynamic provisioning and Z-score. Using dynamic panel dataset includes a sample of 35 HK commercial banks with 134 observations from 2009 to 2014. The results are impressive and most variable I selected are significantly. LLPs are found to be procyclical with a significantly negative relationship with GDPGR during the time period. HK commercial banks smooth their incomes via LLPs, i.e. LLPs are positive significantly related to PROFTA. Capital management via LLPs is found in HK commercial banks with a significantly negative relationship between TRATIO and LLPs. A negative and significant relationship between Lagged LLP and LLP is found in this study, indicating HK banking system uses a very conservative way of provisioning and it is of a counter-cyclical nature. There is a positive significant relationship between Z-score and LLPs, indicating HK commercial banks apply a conservative provisioning practice even when the risk of bankruptcy is decreasing, HK banks still provision more when the amount of total loans increases.